INTERACTIONS OF METHYLOL DERIVATIVES OF UREA WITH Co(II) AND Ni(II) SALTS (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
The reaction between mono- and dimethylolurea with chlorydes of metals Co(II), Ni(II) has been explored. The synthesized connections were investigated by the UR-, NMR-spectrum methods of analysis of elements, and also their magnetic susceptibility is measured.
Keywords: mono- and dimethylolurea; Co(II); Ni(II); magnetic susceptibility